The significance of the human resources role in the hotel sector in Harare, Zimbabwe - Wisikoti, Isaac; Mutanga, Marcus; Nhuta, Stephen (Cosmic Journals, 2016)
There is generally a world wide view that internationally the Hotel and Catering Industry has a number of personnel related problems and poor employment practices and conditions. This view is supported by a study of the Hotel and Catering Industry by {5} which revealed that the industry was dogged with problems of low wages, long working hours and unstable shift hours, poor or non existent career structures, over reliance on informal recruitment methods, lack of evidence of good human resources practices and high labour turnover. Therefore this research sought to assess the level of significance given to the Human Resources function in order to find meaningful solutions to employment practices and personnel problems experienced in the Sector. The research focused on the 1 star to 5 star rated and registered hotels in Harare, Zimbabwe. The hotel ratings are according to the {15} ratings. This study was based on a descriptive survey research design. Both qualitative and quantitative data was collected. For this study a questionnaire was chosen as the data collection instrument. The findings indicated that there was need for a paradigm shift for the HR function from being implementers to formulators of business strategy. The HR function should achieve this by becoming a strategic partner through spending less time on administrative activities and participating more effectively in the hotel processes and activities that define its strategy.